2018
DOI: 10.1590/1678-7757-2017-0451
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine-phosphate-guanosine oligodeoxynucleotides in combination with CD40 ligand decrease periodontal inflammation and alveolar bone loss in a TLR9-independent manner

Abstract: Local administration of toll-like receptor 9 (TLR9), agonist cytidine-phosphate-guanosine oligodeoxynucleotide (CpG ODNs), and CD40 ligand (CD40L) can decrease ligature-induced periodontal inflammation and bone loss in wild type (WT) mouse.Objective:This study aimed to explore whether such effect is dependent on TLR9 signaling.Material and Methods:Purified spleen B cells isolated from WT C57BL/6J mice and TLR9 knockout (KO) mice were cultured for 48 hours under the following conditions: CD40L, CpG+CD40L, CpG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…286 Timely reports have characterized regulatory B cells to play a critical role in suppressing inflammatory responses in vitro 292,293 and ameliorating alveolar bone loss in vivo. [293][294][295] Liu et al performed an in vitro study in which isolated splenic B cells were immunized with P. gingivalis and treated with CD40 ligand and CpG to induce B cell-derived toll-like receptor signaling. 292 Immunized B cells secreted elevated interleukin-10 levels, compared with nonimmunized B cells.…”
Section: B Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…286 Timely reports have characterized regulatory B cells to play a critical role in suppressing inflammatory responses in vitro 292,293 and ameliorating alveolar bone loss in vivo. [293][294][295] Liu et al performed an in vitro study in which isolated splenic B cells were immunized with P. gingivalis and treated with CD40 ligand and CpG to induce B cell-derived toll-like receptor signaling. 292 Immunized B cells secreted elevated interleukin-10 levels, compared with nonimmunized B cells.…”
Section: B Cellsmentioning
confidence: 99%
“…294,296 Zhao et al found that CD40 ligand and CpG induced regulatory B cells ameliorate ligature-induced periodontitis in a toll-like receptor-9-independent manner. 295 Similarly, Shi et al adoptively transferred periodontopathogenic-specific regulatory B cells, which alleviated alveolar bone loss, increased interleukin-10 production, and reduced interleukin-17 and T H 17 cells in the murine gingiva. 297 Advancing knowledge about B cell subsets and their diverse roles in periodontal health and disease will provide opportunity for the development of therapeutic targets in the B cell lineage for the treatment of periodontitis.…”
Section: B Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that certain specific oligodeoxynucleotide (ODN) sequences can inhibit inflammation and reduce alveolar bone resorption. 5,6 ODN can be classified into stimulatory ODN, inhibitory ODN, and inert ODN. Stimulatory ODN generally refers to CpG ODN containing a CG motif.…”
Section: Introductionmentioning
confidence: 99%